2022
DOI: 10.1128/msphere.00331-22
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Temporary Storage Conditions on the Viability of Streptococcus pneumoniae in Saliva

Abstract: For pneumococcal carriage studies, saliva is a sample type that can overcome some of the issues typically seen with nasopharyngeal and oropharyngeal swabs. Understanding the limitations of saliva as a sample type is important for maximizing its use.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Saliva samples were collected from healthy volunteers and screened for the absence of pneumococcus using qPCR targeting piaB , as previously described. 16 Samples negative for both targets were considered negative for pneumococcus and were pooled together. A serotype 19A pneumococcus strain was serially diluted into the pooled saliva, from 5X10 7 CFU/ml to 5X10 1 CFU/mL, in duplicate (Supplementary Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saliva samples were collected from healthy volunteers and screened for the absence of pneumococcus using qPCR targeting piaB , as previously described. 16 Samples negative for both targets were considered negative for pneumococcus and were pooled together. A serotype 19A pneumococcus strain was serially diluted into the pooled saliva, from 5X10 7 CFU/ml to 5X10 1 CFU/mL, in duplicate (Supplementary Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, this leads to lower sample collection burden to study participants (minimizing potential testing aversion), and/or clinical personnel, which is critical particularly in longitudinal studies. Additionally, we have previously demonstrated that encapsulated pneumococci remain viable in raw, unsupplemented saliva with a stable bacterial load seen for 24 hours in the absence of cold-chain transport (i.e., ~19-30°C), 16 further alleviating collection and transport burden for studies conducted in remote or resource-limited settings.…”
Section: Introductionmentioning
confidence: 99%